1973
DOI: 10.1002/iroh.19730580502
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Regulatory Behaviour of Aquatic Ecosystems and its Significance for the Biological Phosphate Removal

Abstract: Bquatic ecosystems have the ability t o compensate for oscillations of the inputs (substrate concentration, dilution rate, temperature). The mechanisms of this buffering capacity are studied in this paper (see fig. 7). The inputs exert an influence on the biomass and the activity of the organisms (activity = specific rate of RNA-synthesis or specific P-removal rate [pg/mg biomass * day]). The activity is regulated either directly by the inputs and/or indirectly by t h e biomass. The activity decreases with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

1975
1975
1977
1977

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…An inverse relationship between biomass and activity per unit biomass (specific activity) may be one of the homeostatic mechanisms which are responsible for this functional stability (BENNDORF u. STELZER 1973, UHLMANN 1973. The lower the biomass, the higher the specific activity.…”
Section: Stubility Of Functional and Structural Ecosystem Criteriamentioning
confidence: 99%
“…An inverse relationship between biomass and activity per unit biomass (specific activity) may be one of the homeostatic mechanisms which are responsible for this functional stability (BENNDORF u. STELZER 1973, UHLMANN 1973. The lower the biomass, the higher the specific activity.…”
Section: Stubility Of Functional and Structural Ecosystem Criteriamentioning
confidence: 99%
“…Another approach, however, is reasonable as well -i. e. biocenoses developed from mixed undefined inocula and adapted to the conditions of a particular experiment. It was found that the "purification effect" of such an experimental system is rather constant (depending mainly on the input parameters such as initial substrate concentration and dilution rate) irrespective of fluctuations and changes in biomass (BENNDORF & STELZER, 1973, CRAMER, 1974.…”
mentioning
confidence: 99%
“…I n den letzten Jahren wurden grundlegende Untersuchungen zur Ermittlung biologischer Zusammenhiinge bei der Veranderung der Wasserbeschaffenheit in Trinkwassertalsperren unter der Zielstellung angestellt, eine Prognose der Beschaffenheit bei Bnderung gewisser wesentlicher Parameter geben zu konnen (HOHNE 1970;UHLMANN, BENNDORF und ALBERT 1971;KLAPPER 1972;HOFMANN 1972;STRAS-XRABA 1973a;BENNDORF und STELZER 1973;BENNDORF 1973). Eine Abstraktion der dargelegten biologischen und biochemischen Zusammenhiinge erfolgte durch die Angabe streng deterministischer mathematischer Gleichungen (BENNDORF 1973;NELSON 1971) und Algorithmen zur Bestimmung einzelner wesentlicher EinfluBfaktoren (STEEL 1972;STRA~KRABA 1973b;DI TORO, O'CONNOR und THOMANN 1971).…”
unclassified